Monitoramento de matriculas, evasões e dependência na escola Lucimar Lima utilizando gráficos estatísticos - GONÇALVES, Fernanda Vitor (2023)
The present study presents a quantitative research about the monitoring of alterations in enrollments, evasion and school dependency in the final grades of elementary education at the Escola Municipal de Ensino Fundamental Lucimar Lima in the municipality of Acará, aiming to analyze, know and represent the number of students enrolled per year. series , total number of students who dropped out and those who passed the school year and continue to depend on morning and afternoon shiftsthrough statistical graphs: bar, line and sector, considering the year 2019, before the pandemic, and the year 2020 in the midst of the pandemic, to then know and visualize the total number of enrolled students who had difficulties and dropped out or who were approved with backlogs in the previous school year during this period. Knowing that statistical graphics are of paramount importance in the analysis, organization, visualization and understanding of data, a bibliographical survey was carried out on important concepts such as bar graphs, pie charts and line graphs, to then carry out the quantitative analysis. of the collected data, which were analyzed, organized in tables and demonstrated through graphical representations using the Power Bi application. Ending with the results and with some considerations on the topic addressed.